2008
DOI: 10.1590/s0101-41612008000400008
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Brazilian public and private water utilities

Abstract: Resumo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…6 Analysis of the performance of Brazilian water supply concessionary companies in the period between 2002 and 2004, showed that public companies were more efficient. 26 A study analyzing the effect of governance on the dynamic efficiency of the water companies also found no robust gain in efficiency following the privatization of utilities. 17 When public companies were analyzed, there was more likelihood of households being connected to water and sewerage networks in municipalities served by government agencies.…”
Section: Discussionmentioning
confidence: 99%
“…6 Analysis of the performance of Brazilian water supply concessionary companies in the period between 2002 and 2004, showed that public companies were more efficient. 26 A study analyzing the effect of governance on the dynamic efficiency of the water companies also found no robust gain in efficiency following the privatization of utilities. 17 When public companies were analyzed, there was more likelihood of households being connected to water and sewerage networks in municipalities served by government agencies.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have examined privatization in the US and UK contexts and provided mixed empirical findings (Bel and Warner ). Some studies have found that costs of water supply services are significantly lower under direct public delivery than under private delivery (e.g., Mann and Mikesell ; Bruggink ; Lynk ; Bhattacharyya et al ; Souza et al ), whereas others have suggested the opposite effect (e.g., Morgan ; Crain and Zardkoohi ; Raffie et al ) or have found no significant difference between the two institutional arrangements with respect to cost savings (e.g., Feigenbaum and Teeples ; Fox and Hofler ; Teeples and Glyer ; Byrnes ; Bhattacharyya et al ; Ashton 2000a, 2000b; Saal and Parker ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The difficulty in providing public sanitation services, in terms of access and quality, are governance challenges to be overcome in the next two decades, as highlighted by several authors [ 9 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Studies in the field reveal a growing preoccupation in better understanding the causes and consequences of efficiency problems in the use of infrastructure, human, and financial resources in this sector, in order to boost development and competitiveness between agencies and sanitation companies.…”
Section: Introductionmentioning
confidence: 99%